The delivery gap : why government projects really fail and what can be done about it - Simcock, Jonathan (Emerald Publishing Limited, 2025)
Sometimes, government has to build something big. Really big. A high-speed railway network, a fleet of nuclear submarines, an IT system big enough for the health records of every person in the country. But Britain has a woeful record of delivering projects of this scale. They are either late, over budget, deliver less than promised - or all three. Some are never completed at all. What is going wrong? In the wake of the cancellation of HS2, Jonathan Simcock, former Major Projects Director of the Office of Government Commerce, provides answers. This eye-opening text draws on testimony from the Ministers, officials and project managers who have tried, and mostly failed, to deliver the country's biggest projects. To face up to its challenges - productivity, growth, national security, and the changing climate - Britain needs huge publicly funded investment. So how do we close the Delivery Gap?
Keywords: Public administration -- Great Britain.; Public investments -- Great Britain.; Political Science -- Public Affairs & Administration.; Public administration.; elektronické knihy; electronic books